The impact of COVID-19 on the physical health, psychological well-being, and financial stability of host and forcibly displaced Myanmar nationals (FDMN) communities - Mst. Roksana Akter; Moudud Ahmad; Shamima Akter; Habiba Akther Jakia; Rafiqul Islam; Touhidul Islam; Md. Kamrul Hasan (Journal of Sustainability, Society, and Eco-Welfare, 2026)
Background: Cox’s Bazar, a coastal district in southern Bangladesh, is highly vulnerable to natural disasters and socio-economic challenges. The region hosts a significant number of forcibly displaced Myanmar nationals (FDMNs) living in overcrowded and resource-constrained conditions. The COVID-19 pandemic has exacerbated existing vulnerabilities in both host and FDMN communities, affecting their physical health, mental well-being, and financial stability. This study explores the multidimensional impacts of the pandemic on these communities. Methods: This qualitative study (Jan–Apr 2022) was conducted in four upazilas of Cox’s Bazar. Data were collected through 16 FGDs and KIIs with about 200 participants from host and FDMN communities. Findings: Survey findings reveal that 73% of respondents reported experiencing COVID-19-related physical symptoms, with fever, dry cough, fatigue, sore throat, and anosmia being the most common. Approximately 61% of participants had mild to severe symptoms, though many recovered without medical intervention. The pandemic also triggered widespread psychological distress. Respondents reported heightened levels of anxiety, depression, loneliness, and uncertainty during the lockdown period. Economically, the impact was equally severe. Loss of income, increased food insecurity, and joblessness were reported by a large portion of the population. The tourism sector, a vital component of Cox’s Bazar’s economy, was significantly disrupted. Conclusion: About 57% of host community members indicated that their livelihoods were directly or indirectly affected by the lockdown and related containment measures. Government and humanitarian agencies must adopt a multidimensional response framework that addresses the physical, psychological, and economic needs of both host and FDMN populations to ensure long-term recovery and resilience. Novelty/Originality of this article: This study compares host and FDMN communities in Cox’s Bazar, assessing COVID-19 impacts across physical, psychological, and financial dimensions.